2014 International Conference on Embedded Computer Systems: Architectures, Modeling, and Simulation (SAMOS XIV) 2014
DOI: 10.1109/samos.2014.6893209
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the temperature bias of power consumption for nanometer-scale CPUs in application processors

Abstract: Abstract-We introduce and experimentally validate a new macro-level model of the CPU temperature/power relationship within nanometer-scale application processors or system-onchips. By adopting a holistic view, this model is able to take into account many of the physical effects that occur within such systems. Together with two algorithms described in the paper, our results can be used, for instance by engineers designing power or thermal management units, to cancel the temperatureinduced bias on power measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…In the study [7], through experiments on real devices it was found that on heterogeneous MPSoCs such as Odroid platforms, power and temperature follows a relationship of quadratic function or exponential function based on various other dependable factors * . We also validate this relationship in Sec.…”
Section: Learning Modulementioning
confidence: 99%
See 1 more Smart Citation
“…In the study [7], through experiments on real devices it was found that on heterogeneous MPSoCs such as Odroid platforms, power and temperature follows a relationship of quadratic function or exponential function based on various other dependable factors * . We also validate this relationship in Sec.…”
Section: Learning Modulementioning
confidence: 99%
“…But in practical sense, majority of the published algorithms lack the flexibility for real world implementation because the usage and workload on similar devices by different users are different and hence, requires the resource management methodologies to be flexible to adapt over time. Elevated temperatures have adverse effects on Integrated Circuits (ICs) and reliability of electronic products can be heavily influenced by spatial or temporal gradients, or absolute temperatures [7]. To mitigate such reliability issues most mobile devices often come with thermal capping.…”
Section: Introductionmentioning
confidence: 99%
“…The power consumed when the terminal is in the Active state is P active M = 3.351 Watt. The Tx/Rx capacity between the mobile handset and the server is B [25]. We assume that the server on which is activated a new VM for each application offloading is equipped with a X86 CPU operating 4 times faster than the CPU of the mobile terminal (F ).…”
Section: A Mobile Terminal and Server Characteristicsmentioning
confidence: 99%
“…Elevated operating temperatures and thermal cycling on the device have adverse effects on Integrated Circuits (ICs) and reliability of electronic products can be heavily influenced by spatial or temporal gradients or absolute temperatures [8]- [10]. Here, thermal cycling is the phenomenon of the operating temperature increasing from an initial value and then decreasing to the starting value periodically, and each occurrence of the phenomenon is signified as one thermal cycle.…”
Section: Introductionmentioning
confidence: 99%